Proceedings of the 1989 26th ACM/IEEE Conference on Design Automation Conference - DAC '89 1989
DOI: 10.1145/74382.74442
|View full text |Cite
|
Sign up to set email alerts
|

Parallel pattern fault simulation of path delay faults

Abstract: This paper presents an accelerated fault simulation approach for path delay faults. The distinct features of the proposed fault simulation method consist in the application of parallel processing of patterns at all stages of the calculation procedure, its versatility to account for both robust and non-robust detection of path delay faults, and its capability of efficiently maintaining large numbers of path faults to be simulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…The improvements and new techniques described in this paper are based on the robust path delay fault simulation of Smith [2] and its extension to nonrobust simulation introduced by S c h ulz et al [6].…”
Section: Path Delay F Ault Simulationmentioning
confidence: 99%
See 4 more Smart Citations
“…The improvements and new techniques described in this paper are based on the robust path delay fault simulation of Smith [2] and its extension to nonrobust simulation introduced by S c h ulz et al [6].…”
Section: Path Delay F Ault Simulationmentioning
confidence: 99%
“…Each v alue consists of the nal boolean value f0; 1g and the detectability status fs; p; g. A detectability status s indicates that a signal remains stable at its nal value, p shows that there is at least one path from a primary input that is path delay fault testable, and indicates that the detectability status of a signal is neither s nor p. The value propagation table for an OR gate and an inverter are shown in Table 1. Analogous propagation tables can be derived for AND and XOR gates [2,6]. _ 0s 1s 0p 1p 0 1 0s 0s 1s 0p 1p 0 1 1s 1s 1s 1s 1s 1s 1s 0p 0p 1s 0p 1 0p 1 1p 1p 1s 1 1 1 1 0 0 1s 0p 1 0 1 1 1 1s 1 1 1 1 : 0s 1s 1s 0s 0p 1p 1p 0p 0 1 1 0 Table 1: Robust propagation table for OR-and NOT-gates Schulz et al [6] showed that it is possible to collapse the six values to four values, if only nonrobust fault detection is required.…”
Section: Path Delay F Ault Simulationmentioning
confidence: 99%
See 3 more Smart Citations